Determining the optimal isoleucine:lysine ratio for the 25 to 50 lb pig - J R Bergstrom; J A Loughmiller; R E Musser; W B Nessmith Jr; Jim L Nelssen; Michael D Tokach; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1996)
A 21-day growth trial was conducted to determine the isoleucine: lysine ratio necessary to optimize growth performance of the 25 to 50 lb nursery pig reared in a segregated early-weaning (SEW) system. Ten experimental diets, including two levels of lysine (.75% and 1.10% digestible lysine) and five apparent digestible isoleucine:lysine ratios (45, 50, 55, 60, and 65%), were used in a 2 x 5 factorial arrangement. Growth performance was improved by feeding 1.10% rather than .75% digestible lysine. Also, results indicated that the apparent digestible isoleucine requirement for the SEW-reared, 25 to 50 lb pig is approximately .50% of digestible lysine.; Swine Day, Manhattan, KS, November 21, 1996
Keywords: Swine day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 772; Swine; Early-weaned pigs; Amino acids; Isoleucine